2005
DOI: 10.1128/jcm.43.2.1009.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium fortuitum Infection after a Brown Bear Bite

Abstract: A 56-year-old male was admitted to the hospital after a bear attack. A wounded brown bear (Ursus arctos) had attacked the patient. The patient had several bite wounds. The most serious wound was a deep penetrating bite wound in his left thigh. This wound needed immediate debridement, and ceftriaxone prophylaxis was commenced. The wound penetrated the fascial planes. All necrotic tissues and foreign material were surgically removed, and the wound was left open. The patient's wounds required redebridements on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 4 publications
(3 reference statements)
0
12
0
Order By: Relevance
“…Carnivore attacks are characterized by the combined occurrence of injuries (including puncture wounds, lacerations, avulsions, and bone fractures (Baliga et al 2012)), crushing, and penetrating trauma (Agarwal et al 2011). Humans attacked by large carnivores are consequently at risk of suffering blunt and penetrating trauma caused by teeth, paws, and claws, which may lead to a local infection (Capitini et al 2002;Kunimoto et al 2004;Lehtinen et al 2005;Türkmen et al 2012) because wounds are often contaminated with a variety of pathogens (polymicrobial infection) such as Pasturella multocida and others (Kizer 1989;Isotalo et al 2000;Linnell et al 2002;Abrahamian and Goldstein 2011). Fatal attacks are common, especially in Africa and Asia (Conrad 1992), although many cases are reported in which victims survive a violent encounter with a carnivore (Agarwal et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Carnivore attacks are characterized by the combined occurrence of injuries (including puncture wounds, lacerations, avulsions, and bone fractures (Baliga et al 2012)), crushing, and penetrating trauma (Agarwal et al 2011). Humans attacked by large carnivores are consequently at risk of suffering blunt and penetrating trauma caused by teeth, paws, and claws, which may lead to a local infection (Capitini et al 2002;Kunimoto et al 2004;Lehtinen et al 2005;Türkmen et al 2012) because wounds are often contaminated with a variety of pathogens (polymicrobial infection) such as Pasturella multocida and others (Kizer 1989;Isotalo et al 2000;Linnell et al 2002;Abrahamian and Goldstein 2011). Fatal attacks are common, especially in Africa and Asia (Conrad 1992), although many cases are reported in which victims survive a violent encounter with a carnivore (Agarwal et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Lehtinen et al reported a case of a 56-year-old male who sustained several bite wounds from a brown bear (Ursus arctos) (145). Bacterial cultures from a deep thigh bite wound grew Streptococcus sanguis, Neisseria sicca, Bacillus species, and Mycobacterium fortuitum.…”
Section: Rare Infectious Diseases In Humans Acquired From Cats and Domentioning
confidence: 99%
“…Data for the oral bacteriology of bears as well as bear bite wounds in humans are limited to a few studies and case reports (79,140,145,175,193). Organisms isolated from grizzly or black bear oral cavities have included Streptococcus (61%), Staphylococcus (48%), Escherichia (40%), Enterobacter (25%), Citrobacter (10%), Hafnia (10%), Proteus (6%), and Acinetobacter (6%) species (175).…”
Section: Rare Infectious Diseases In Humans Acquired From Cats and Domentioning
confidence: 99%
“…Most studies have involved oral bacteria of bears or bacteria associated with bear bite wounds (Parry et al, 1983;Goatcher et al, 1987;Kunimoto et al, 2004). The only reported nontuberculous mycobacterium from any bear species is M. fortuitum that was isolated from a brown bear (Ursus arctos) bite wound (Lehtinen et al, 2005).…”
mentioning
confidence: 99%